Novel approach to assess sarcopenia in children with inflammatory bowel disease - Kriszta Katinka Boros; Gábor Veres; Gábor Veres; Hajnalka Krisztina Pintér; Éva Richter; Áron Cseh; Antal Dezsőfi; András Arató; George S. Reusz; Dóra Dohos; Dóra Dohos; Katalin E. Müller; et al. (Frontiers Media S.A., 2024)
IntroductionSarcopenia is associated with poor clinical outcomes in chronic diseases. Our study aimed to characterize body composition (BC) parameters in patients with inflammatory bowel disease (IBD) and compare skeletal muscle mass (SMM) parameters with the healthy pediatric population.MethodsBC of healthy controls (HC) and of patients with IBD were measured via multifrequency bioelectrical impedance (InBody 720 device) in a cross-sectional manner. The effect of sex, age, height, weight, and body mass index (BMI) on BC parameters, with a special attention to SMM, was assessed. Reference tables from SMM were generated using a maximum-likelihood curve-fitting technique for calculating Z scores.ResultsBC parameters were associated with age, body size, and sex. SMM was lower in patients with IBD (n = 57, aged 6.71 ± 8.7 years) compared to unadjusted HC (n = 307, aged 9.9-19.3 years; 143 males; SMM: 22.34 ± 8.38 vs. 24.4 ± 6.3 kg; p = 0.03). SMM showed a moderately strong correlation with age, weight, height, and BMI (R = 0.65, 0.9, 0.87, and 0.66; p < 0.05 for each) in HC. In multivariate stepwise, ridge regression analysis, age, sex, and BMI remained the significant predictors of SMM (age β = 0.47, −0.31, and 0.38, respectively; p < 0.05). SMM of sex-, age-, and BMI-adjusted HC did not differ from IBD. Therefore, BMI Z score-based references were plotted for normalizing SMM, and SMM Z score was calculated and found to be similar to that of HC.ConclusionsBC is supposed to be an easy-to-measure and objective marker of sarcopenia in children with IBD. Adjustment of SMM for BMI Z score might be needed to avoid the overestimation of sarcopenia in this patient population.